KECEPATAN MEMBACA EFEKTIF TEKS EKSPOSISI SISWA KELAS X IPS SMA NEGERI 8 PEKANBARU - Puja Nur Ayu; M. Nur Mustafa; Abdul Razak (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This paper aims to describe the effective speed of readingthe exposition text of Social Sciences class X Pekanbaru 8 High School students, and describes the comparison of the effective reading speed of the exposition text per group of Social Sciences class X students of SMA 8 Pekanbaru through a set of test tools, namely objective tests containing two texts exposition and 20 items. The method used in this research is quantitative research, which results in the conclusion that the effective reading speed of the exposition text of class X SMAN 08 Pekanbaru is very low in category and the effective reading speed of exposition text of class X SMAN 08 Pekanbaru per sample group is not the same (different).Key Words: Effective reading speed, exposition text.